2007
DOI: 10.1177/0267659107080877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying nitric oxide release to prevent platelet consumption and preserve platelet function in an in vivo model of extracorporeal circulation

Abstract: The gold standard for anticoagulation during extracorporeal circulation (ECC) remains systemic heparinization and the concomitant risk of bleeding in an already critically ill patient could lead to death. Normal endothelium is a unique surface that prevents thrombosis by the release of antiplatelet and antithrombin agents. Nitric oxide (NO) is one of the most potent, reversible antiplatelet agents released from the endothelium. Nitric oxide released from within a polymer matrix has been proven effective for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 21 publications
4
76
0
Order By: Relevance
“…Norel-b coating with a top coating of PVC/DOS was used as an ECC circuit of a rabbit arteriovenous shunt model. Compared to bradykinin-stimulated endothelial NO flux (1.6-4.0 Â 10 À 10 mol cm À 2 min À 1 ) and basal endothelial NO flux (0.5 Â 10 À 10 mol cm À 2 min À 1 ) [145], the Norel-b coating had NO fluxes of 2.3, 13.7, 20.6 and 39.1 Â 10 À 10 mol cm À 2 min À 1 of 2, 10, 25, and 50 wt% of DBHD/N 2 O 2 , respectively [144]. All Norel-b coatings except 2 wt% were able to maintain activated clotting time within the baseline and protect the platelet count over the course of 4 h. SEM images showed a significant amount of platelet adhesion and activation for the control groups while few platelets adhered to Norel-b coatings.…”
Section: Extracorporeal Circulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Norel-b coating with a top coating of PVC/DOS was used as an ECC circuit of a rabbit arteriovenous shunt model. Compared to bradykinin-stimulated endothelial NO flux (1.6-4.0 Â 10 À 10 mol cm À 2 min À 1 ) and basal endothelial NO flux (0.5 Â 10 À 10 mol cm À 2 min À 1 ) [145], the Norel-b coating had NO fluxes of 2.3, 13.7, 20.6 and 39.1 Â 10 À 10 mol cm À 2 min À 1 of 2, 10, 25, and 50 wt% of DBHD/N 2 O 2 , respectively [144]. All Norel-b coatings except 2 wt% were able to maintain activated clotting time within the baseline and protect the platelet count over the course of 4 h. SEM images showed a significant amount of platelet adhesion and activation for the control groups while few platelets adhered to Norel-b coatings.…”
Section: Extracorporeal Circulationmentioning
confidence: 97%
“…The results showed that NO-releasing circuits greatly suppress platelet adhesion and activation and did not exhibit apparent thrombus formation compared to controls. Annich and co-workers prepared another polymer coating called Norel-b that contains DBHD/N 2 O 2 , PVC/DOS and KTpClPB, to explore the critical flux necessary to protect platelet count and function and to inhibit platelet activation [143,144]. Norel-b coating with a top coating of PVC/DOS was used as an ECC circuit of a rabbit arteriovenous shunt model.…”
Section: Extracorporeal Circulationmentioning
confidence: 99%
“…Recently, efforts have begun to be explored in the laboratory to incorporate NO-releasing polymers in the ECMO circuit [98] and to provide NO in the sweep gas [99,100,101]. The reasoning for its use in the setting of extracorporeal life support is that the half-life is so short (2-6 sec) that only a local effect occurs [102]. This is the goal of the coated circuits where the anticoagulation activity is sequestered to the artificial surfaces and does not act systemically.…”
Section: Nitric Oxidementioning
confidence: 99%
“…This is the goal of the coated circuits where the anticoagulation activity is sequestered to the artificial surfaces and does not act systemically. In vitro and animal studies of the use of NO on ECMO circuits have demonstrated a significant improvement in platelet functionality and retention of platelets with minimal generation of the undesirable side effects of nitric oxide infusion, specifically methemoglobin [100,101,102]. The primary downsides to this type of therapy are the lack of current devices, which can accurately dose nitric oxide through the membrane, and the high cost of nitric oxide therapy.…”
Section: Nitric Oxidementioning
confidence: 99%
“…23,24 Polymers that release nitric oxide are an extremely promising solution to the problem. 25,26 Although Gibbons's pump and Kolobow's spiral coil silicone membrane oxygenator remain in use today, the centrifugal pump has emerged as an alternative. The centrifugal pump can be miniaturized and is the pump of choice for emergency deployment in resuscitations and for patient transport.…”
Section: To the Bedside: Development Of Clinical Applicationsmentioning
confidence: 99%